PERAN DINAS SOSIAL KABUPATEN KARIMUN DALAM MENDUKUNG PELAKSANAAN AKREDITASI LEMBAGA KESEJAHTERAAN SOSIAL ANAK TAHUN 2022-2023 - ', Sulastri; Nasution, Hazqon Fuadi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2024)
The existence of a Child Social Welfare Institution (LKSA), in this case an orphanage, is not determined by the number of children who receive services, but the measure is the accreditation of the LKSA. Accreditation of Social Welfare Institutions (LKS) is an effort to measure the level of appropriateness of services and standards for institutions in the field of social welfare. The aim of this research is to determine the role of the Social Service in supporting the implementation of LKSA accreditation in Karimun Regency in 2022-2023, as well as to find out what obstacles factors are experienced by the Social Service in supporting the implementation of LKSA accreditation in Karimun Regency. The theory used in this research is about the Role of Government with indicators of Government as Regulator, Government as Dynamisator, and Government as Facilitator. The research approach used is a qualitative approach. This type of research is descriptive. The research location is at the Karimun Regency Social Service. The types and sources of research data are divided into primary data using purposive sampling techniques and secondary data in the form of supporting data related to the implementation of LKSA accreditation. Data collection techniques were used by means of interviews and documentation. The results of this research are that the role of the Social Service in supporting the implementation of accreditation for Child Welfare Institutions (LKSA) can be said to have not run optimally because there are still several obstacle factors in assisting the process of implementing this accreditation, namely limited budget funds, limited time and frequency of socialization, lack of facilities and inadequate infrastructure and facilities, as well as a lack of understanding and knowledge from LKSA managers regarding accreditation. Keywords : Role, Child Social Welfare Institution, Accreditation